Catalytic Performance of Mx(M = Ni, Co, Cu)Oy/(MgO)0.9(CeO2)0.1 for Combustion of Methane - Zheng, Shu; Guo, Yuhua (Asian Journal of Chemistry, 2012)
A series of catalysts Mx(M = Ni, Co, Cu)Oy/(MgO)0.9(CeO2)0.1 have been prepared by a sol-gel method. The effect of the activity of Mx(M = Ni, Co, Cu)Oy/(MgO)0.9(CeO2)0.1 on combustion of methane was investigated and characterized by BET, XRD and TEM techniques. In view of activity and stability of a catalyst, NiO/(CeO2)0.1-(MgO)0.9 catalyst shows the highest catalytic activity and the best thermal stability for methane combustion. The structure of the catalyst calcined at 1000 ºC does not have any change, only size increases slightly from TEM photos. It still has a specific surface area of 14.32 m2 g-1 and high activity as well as good thermal stability.